Analyze of Adherence Treatment Factors in Drug Resistance Tuberculosis Patient with Acid Resistant Bacillus Conversion - Afriani, Dina; Edianto, Edianto (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Treatment adherence is one of the treatments for Resistant Tuberculosis (TB RO) Drug that is a concern, the method used in this study is cross-sectional using purposive sampling techniques. A total of 104 respondents with TB RO were being treated at the hospital. H. Adam Malik. Patient data came from the SITB of TB RO patients and was collected using TB MAS (TB-Medication Adherence Scale). The results of the study found that as many as 37 respondents (36.4%) were declared non-compliant and as many as 70 respondents (67.3%) were declared compliant. The purpose of this study is to see the relationship between adherence and BTA conversion in TB RO patients and to find out the factors that affect treatment adherence of TB RO patients. The results of this study found a relationship between patient compliance and BTA conversion with a p.value of 0.003. A bivariate analysis with chi-square was carried out and found that the factors that affect treatment compliance in TB RO patients are health service communication factors (0.000), personal traits (0.000), self-confidence (0.000), social support (0.000) and access to services (0.000). The higher the level of compliance, the higher the expected success rate of therapy, so that communication of health workers, social support and personal beliefs and access to good service facilities are required.